Liquidity and Profitability Ratio Analysis for Measuring The Financial Performance of PT. Bank Bri Syariah 2012 - 2019 Period - Nurwita; Maria Ningsih (Kusuma Negara Business School, 2020)
This research was purposed to the financial performance of PT. Bank BRI Syariah, which is measured using liquidity ratios and profitability ratios based on reporting data from 2012 to 2019. This research uses a descriptive approach, namely methods carried out by collecting, clarifying, analyzing and comparing them with the banking industry standards set by Bank Indonesia through SEBI No. 6/10 / PBU Date 12 April 2004 and the Financial Services Authority through SPI Vol.16 No.10 September 2018 to take take. Based on the results of research and discussion, the financial performance of PT. Bank BRI Syariah, Tbk. measured using the liquidity ratio if calculated from the total average, for the Quick Ratio it shows the condition of the bank is not healthy, because the percentage value of the ratio is below Bank Indonesia standards, but for Current ratio and Cash Ratio it shows the condition of the bank is healthy, because the percentage value is in based on Bank Indonesia standards. Meanwhile, the financial performance of Bank BRI Syariah is measured by using the profitability ratio if calculated from the total average, for Return on Assets, Return on Equity, BOPO as a whole shows the condition of the bank is not healthy, because the percentage value of the ratio is below the standards of the Financial Services Authority.